Growth Rates and Characteristics of Ice on the Ottauquechee and Winooski Rivers of Vermont During Winter 1977-78. - Deck,David (1978)
Ice thickness, growth rates and characteristics of river ice are tabulated for use with a planned physical hydraulic model of the Ottauquechee River in Quechee, Vermont, using real ice. (Author)